The leadership training activity book 50 exercises for building effective leaders - Hart, Lois Borland (AMACOM, 2005)
Gives trainers information they need to teach and apply leadership competencies participants need. Featuring adaptable exercises on a range of leadership topics, this collection of activities is an all-in-one resource for trainers seeking to prepare leaders.